2019
DOI: 10.3390/s19235326
|View full text |Cite
|
Sign up to set email alerts
|

Velocity Control of Traveling-Wave Ultrasonic Motors Based on Stator Vibration Amplitude

Abstract: Nonlinearity and resonance frequency shift make it difficult to control the operation of the traveling-wave ultrasonic motors (TWUSMs) in a wide velocity and load range. In this paper, a velocity control scheme based on the stator vibration amplitude and the parallel resonance frequency (VCBVF) of TWUSMs is proposed. Then, the stator vibration amplitude (SVA) and parallel resonance frequency (fp) are detected by a transformer ratio-arm bridge. Based on the linear relationship between the velocity and the SVA o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…The working principles of LUSMs and rotary ultrasonic motors are similar, so in order to achieve the VBSC, a transformer ratio arm bridge (TRAB) is used to detect the SVA [ 19 ]. The parallel equivalent circuit model of the single-phase PZT ceramic of the LUSM and the schematic diagram of the TRAB are shown in Figure 2 .…”
Section: Theoretical Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The working principles of LUSMs and rotary ultrasonic motors are similar, so in order to achieve the VBSC, a transformer ratio arm bridge (TRAB) is used to detect the SVA [ 19 ]. The parallel equivalent circuit model of the single-phase PZT ceramic of the LUSM and the schematic diagram of the TRAB are shown in Figure 2 .…”
Section: Theoretical Analysismentioning
confidence: 99%
“…However, for LUSMs, the slider position change is not associated with the input voltage, so this method is not suitable for LUSMs. Fang et al [ 19 ] found that the transformer tap voltage of the transformer ratio arm bridge is linear to the rotor speed of the rotary ultrasonic motor. Therefore, the rotor speed can be estimated according to the transformer tap voltage.…”
Section: Introductionmentioning
confidence: 99%
“…For model A, which is similar to the classic Butterworth-Van Dyke (BVD) model [ 20 , 21 ], the series , and characterize the modal damping, mass and stiffness, respectively. Under the steady state of sinusoidal excitation, the model A can be converted to the model B [ 19 ]. In this model, the parameters can be calculated by where …”
Section: Electrical Architecturementioning
confidence: 99%
“…However, these schemes require complicated software operations to calculate the frequency deviation and the vibration amplitude. With the aid of a transformer ratio arm bridge (TRAB), a vibration amplitude signal is obtained online in an ultrasonic motor control scheme under different operating conditions [ 19 ]. Moreover, this signal is in phase with the excitation current at , so the parallel resonance detection can be achieved by detecting the phase between the vibration and the excitation current signals.…”
Section: Introductionmentioning
confidence: 99%
“…[26,27] Recently, there have been breakthroughs in the open-loop control technology of ultrasonic motors, which carry great significance for some applications in which it is difficult to develop closed-loop control, such as cell slice actuators, ear surgical equipment, and magnetic compatible tactile interfaces. [28][29][30][31] In this paper, application of ultrasonic motors in aerospace, optical, biomedical, and precision engineering is surveyed. Some technological breakthroughs and corresponding problems caused by new materials and technologies are then discussed.…”
Section: Introductionmentioning
confidence: 99%